Prefrontal oxygenation during experimental pain in adolescents engaging in non-suicidal self-injury - Mürner-Lavanchy, Ines M.; Kao, Han-Tin; Sele, Silvano; Koenig, Julian; Kaess, Michael (Journal of affective disorders, 2025)
Background - The intricate role of pain in non-suicidal self-injury (NSSI) makes the investigation of alterations in brain function during pain processing a critical yet underexplored topic. The aim of this study was to investigate fNIRS correlates of experimental pain and how these differed between adolescent patients engaging in NSSI and healthy controls. - Methods - 154 adolescent patients with NSSI and 48 healthy controls underwent a heat pain stimulation with linearly increasing temperature from 32 °C to max. 50 °C, during which fNIRS activity was recorded. Associations between fNIRS activity and pain perception (i.e. pain threshold, pain tolerance and pain intensity) were examined using linear mixed models and linear regression analyses. - Results - Across groups, we found a decrease in prefrontal oxygenation during increasing pain stimulation: Oxygenated hemoglobin was higher during baseline than during pain threshold (b = −0.36, p < .001) and higher during pain threshold than during pain tolerance (b = −0.10, p < .001). We did not find differential patterns of prefrontal oxygenation across the pain assessment between patients and healthy controls. Also, no association between pain intensity and fNIRS activity was found. - Limitations - fNIRS was only recorded in prefrontal regions and our design did not include a non-painful stimulation as a control condition. - Conclusion - While our study adds to the understanding of prefrontal hemodynamic changes associated with pain processing, it did not contribute further evidence to the few existing findings regarding altered neural processing of pain in adolescents engaging in NSSI.
Online verfügbar: 22. Oktober 2024, Artikelversion: 07. November 2024
Gesehen am 22.05